MAKING BIODEGRADABLE PLASTIC FROM SEAWEED BY OVEN DRYING METHOD - Putnarubun, Cenny; Renur, Nini Munirah; Ngabalin, Daniel; Leunupun, Dirk (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2025)
Biodegradable plastic is an environmentally friendly plastic that can be decomposed by microorganisms. This study aims to produce bioplastics from seaweed Eucheuma cottonii using the oven drying method and to analyze the resulting physical properties. The study was carried out through several stages: sample preparation, filtrate production, mixing of additives (acetic acid and glycerol), casting, and drying in an oven at 80 °C with drying times varying from 4 to 18 hours. The results showed that 4 hours of oven drying produced bioplastics with a thin and flexible texture, while longer drying times resulted in darker colors and brittle textures. Water resistance tests showed that ovendried bioplastics decomposed faster than those dried under sunlight. Thus, oven drying is effective for accelerating bioplastic production, although the optimal quality is still influenced by heating duration.